NON-ENGLISH DEPARTMENT STUDENTS' READINESS IN FLIPPED-CLASSROOM OF BLENDED LEARNING - Valentina Dyah Arum Sari; Heribertus Binawan; Lu’luil Maknun (LPSDI Bina Patria, 2023)
Blended-learning is able to provide students with an independent learning atmosphere and also a learning environment that facilitates their respective learning styles so that later they can achieve their learning goals more easily. The non-English department students are required to take the English course. After almost two years of experiencing full online learning, currently learning English is given in a blended-learning manner. Following the initial assumptions, maybe this will be a win-win solution in this transition period. To provide the best, an approach namely Flipped-Classroom was applied to English classes for non-English Department Students. The research aimed to answer the following question: How is the non-English Department students’ readiness in Flipped-Classroom of Blended Learning? The research was mixed-method research. The results of the study revealed that the students’ readiness analyzed from seven categories obtaining 65,99%. This percentage showed medium qualification. Furthermore, non-English Department students’ readiness in Flipped-Classroom of Blended Learning was in medium level.